Heritage and hesitancy: how preference for traditional Chinese medicine influences vaccine attitudes - Yaxin Lan; Yaxin Lan; Lei Jin (Frontiers Media S.A., 2024)
IntroductionVaccine hesitancy, amplified by the COVID-19 pandemic, is a pressing public health challenge. This study investigates the association between Traditional Chinese Medicine (TCM) preference and COVID-19 vaccine hesitancy within China.MethodsThe study uses data from the 2021 Chinese General Social Survey (CGSS) (N = 2,690). Logistic regressions and Karlson-Holm-Breen (KHB) method are employed to analyzed the relationship between TCM preference and vaccine hesitancy.ResultsThe study reaffirms prior findings by revealing a robust and stable association between TCM preference and vaccine hesitancy, which remains unaffected by socioeconomic and demographic confounders, as well as institutional trust dynamics of healthcare system. Contrary to expectations, TCM enthusiasts do not exhibit vaccine hesitancy based on divergent epistemological views concerning vaccine risks and immunity acquisition compared to biomedicine.DiscussionThis research enriches understandings of the intricate relations between healthcare paradigms and vaccine attitudes, inviting further inquiry into the role of CAM in shaping vaccination behaviors across different cultures and contexts. The insights bear significant public health implications for enhancing vaccine acceptance and coverage, particularly among populations where CAM practices wield substantial influence.